Perbuatan Melawan Hukum Oleh Individu Atas Konten Tiktok Tentang Perpindahan Ke Suatu Daerah: Tinjauan Pasal 1365 Kuhperdata - Zaqia Salsabillah; Muhammad Jibran Arief (GLOBAL SCIENTS PUBLISHER, 2026)
The development of social media, especially the TikTok platform, provides a space for the public to disseminate information quickly. However, content that is inaccurate or damages the image of a region can cause immaterial losses for the community and local government. This study aims to analyze unlawful acts regarding TikTok content that harms the image of a region based on Article 1365 of the Civil Code. The research method used is normative legal research with statutory and conceptual approaches. The results of the study indicate that content containing false information and causing loss can be qualified as an unlawful act if it meets the elements of Article 1365 of the Civil Code. Thus, the aggrieved party can claim compensation against the perpetrator of the content dissemination.